The Effect of Single Leg Stance Training on Static and Dynamic Balance in Obese Students - Raharja, Dimetry Pambuka; Hayati; Pelamonia, Shandy Pieter; Darisman, Eka Kurnia (PENJAGA : Pendidikan Jasmani dan Olahraga, 2026)
This study aimed to examine the effect of Single Leg Stance training on balance among obese students in the Physical Education Study Program at Universitas PGRI Adi Buana Surabaya. The focus of the study included static balance, measured using the Standing Stork Test, and dynamic balance, assessed using the Y Balance Test. The research employed a quantitative experimental method with a pre-test and post-test control group design. The participants were divided into two groups: an experimental group that received Single Leg Stance training for six weeks (12 sessions) and a control group that did not receive any specific treatment. Data were analyzed using a paired sample t-test with a significance level of 0.05. The results indicated that Single Leg Stance training had a significant effect on improving static balance in the experimental group, as shown by a significance value (Sig. 2-tailed) of 0.000 (< 0.05). However, the training did not demonstrate a significant effect on dynamic balance, with a significance value of 0.051 (> 0.05). Based on these findings, it can be concluded that Single Leg Stance training is more effective in improving static balance than dynamic balance among obese students.